Mitochondrial Proton Leak Compensates for Reduced Oxidative Power during Frequent Hypothermic Events in a Protoendothermic Mammal, Echinops telfairi - Polymeropoulos, Elias T.; Oelkrug, R.; Jastroch, M. (Frontiers in Physiology, 2017)
The lesser hedgehog tenrec (Echinops telfairi) displays reptile-like thermoregulatory behavior with markedly high variability in body temperature and metabolic rate. To understand how energy metabolism copes with this flexibility, we studied the bioenergetics of isolated liver mitochondria from cold (20 °C) and warm (27 °C) acclimated tenrecs. Different acclimation temperatures had no impact on mitochondrial respiration using succinate as the substrate. Mimicking the variation of body temperature by changing assay temperatures from 22 °C to 32 °C highlighted temperature-sensitivity of respiration. At 22 °C, the reduction of respiratory control ratio (RCR, 40% compared to 32 °C), a common estimate for mitochondrial efficiency, was caused by reduced substrate oxidation capacity. The precise assessment of efficiency with corrected respiration rates is enabled by the simultaneous measurement of mitochondrial membrane potential. Using this method, we show that acclimation temperature had no effect on respiration driving the proton leak at the highest common membrane potential, but lowering assay temperature decreased proton leak respiration. Using membrane potential corrected values, we show that the fraction of ATP-linked respiration (coupling efficiency) was maintained (70-85%) at lower temperatures. Collectively, we demonstrate that compromised substrate oxidation was temperature-compensated by the reduction of proton leak, thus maintaining the efficiency of mitochondrial energy conversion. The integrated membrane potential data suggest that adjustments of mitochondrial proton leak contribute to energy homeostasis during thermoregulatory flexibility of tenrecs.